Infodemic, disinformation and fake news: the role of libraries in Post-Truth Society - Revez, Jorge (2022)
This study’s purpose is to systematically review the literature to identify the most recent library practices against fake news. Previous findings showed most studies emphasize academic libraries practices and are mainly focused on information literacy instruction. This article updates prior research aiming to acknowledge the tangible practices of libraries, discuss their efficiency, and continue a categorization of those practices. It was performed a systematic literature review of the last 12 months (October 2020-September 2021) to retrieve the most recent library practices. After the extraction, with a final set of 17 documents, a multi-step qualitative analysis, and a categorization were developed. The current debate is still around information literacy strategies that intend to reiterate an authority-based source evaluation versus the challenge to recognize an emotional-based reaction to fake news in a post-truth world. The role of libraries is cornered in an instructional framework, while disinformation is pervasive in several information ecosystems. The role of libraries in a Post-truth society is still an open debate, yet there is almost a consensus that libraries should engage in partnerships and be part of a multidisciplinary approach.